Analysis of Consumer Profiles and Business Models in Rumah Tropis Using Empathy Maps and Business Model Canvas - Rahman, Askur (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): Juni, 2022)
This study aims to recognize the needs and desires of users regarding products from Rumah Tropis using empathy maps and analyze the business models of products from Rumah Tropis using Business Model Canvas (BMC). Data excavation is conducted by interviewing related parties and then analyzing using empathy maps and Business Model Canvas (BMC). The results showed that vegetable consumers have a variety of vegetables that are not fresh, dirty, and contain pesticides. The expectation of affordable prices can be directly delivered to consumers' places and served in a friendly manner. Furthermore, the advantages of vegetable products are created by offering vegetables with guaranteed quality (fresh vegetables, hygienic and pesticide-free), prices are more affordable than the modern market and committed to providing friendly services to obtain the desired income stream.